Nawab Sultan Jahan Begum: A Pioneer of Muslim Women’s Education in Colonial India - Razia Sultana (Penerbit Hellow Pustaka, 2025)
This paper explores the life, contributions, and legacy of Nawab Sultan Jahan Begum—one of the most visionary and reformist Muslim women leaders in the Indian subcontinent during the late 19th and early 20th centuries. As the ruler of the princely state of Bhopal, she played a pioneering role in promoting female education, public health, social reform, and women's empowerment. Through the establishment of educational institutions, development of a culturally sensitive yet modern curriculum, and authorship of over forty scholarly works, she laid the groundwork for a balanced synthesis of Islamic values and modern education. Her contributions were not confined to her state but impacted the broader Muslim society, especially in the field of women’s intellectual and social awakening. This study examines her personal life, educational philosophy, institutions, literary works, and the lasting impact of her reformist agenda.